Petrographic and Geochemical Characteristics of the Djabatoure Massif Metamagmatites from Pan-African Orogen in Togo, West Africa - Malibida Kpanzou, Sarakawa Abalo; Alayi, Gnanwasou; Agbossoumonde, Yao; Tairou, Mahaman Sani; Gonzalez-Jimenez, José MarÃa; Garcia-Casco, Antonio (European Scientific Journal, ESJ, 2023)
The Dahomeyide orogen in Togo and adjoining parts of SE-Ghana and Benin records the suture of West Africa Craton (WAC) into NW Gondwana. The suture zone corresponds to a narrow and lithologically diverse area with HP granulites complexes. In Togo, the Djabatoure massif, located in the central part of Togo, belongs to the suture zone. The aim of this paper is to present the petrographic and geochemical characteristics of the Djabatoure massif in order to understand its implication in the geodynamic evolution of the Dahomeyide belt in Togo. The methodology implemented is based on a synthesis of previous works, a petrographic study of twenty thin sections and a geochemical study through discrimination diagrams of fifteen samples. The result shows that the Djabatoure massif is composed of granulites, pyroxenites, amphibolites, talcschists and gneisses. These rocks were equilibrated under granulite facies conditions and subsequently partially retrogressed to amphibolite facies. They display tholeiitic affinity, enriched LREE and negative anomalies in Nb, Zr and Ti indicating subduction zone magma. These features are consistent with protoliths of tholeiites, N-MORB and volcanic arc basalts affinities. The Djabatoure massif rocks were set up in oceanic environment and are thought to have been derivated from a metasomatized mantle.